Gastric teratoma invasion and bulb fistula formation in an adult: report of one case and literature review. Issue 11 (November 2019) - Lu, Bei; Yang, Lili
Gastric teratoma primarily occurs within 3 months following birth, and is a rare pattern of gastric lesion in adult patients. The present study reports the case of a 60-year-old male patient who was diagnosed with a tumour in the lesser curvature within the gastric cardia area, which grew outside the cavity, invaded into the duodenal bulb and formed a gastroduodenal fistula. Briefly, initial gastroscopy upon hospital admission revealed mucosa bulging into the gastric cavity, gastric ulcer and duodenal bulb mucosal congestion with oedema. Subsequent computed tomography scans showed lesser curvature-occupying hamartoma in the gastric cardia area, and upper gastrointestinal angiography confirmed gastric stromal tumour complicated with cardia duodenal fistula. Total gastrectomy followed by Roux-en-y oesophagojejunostomy was performed, and pathology analysis of the tissue specimen confirmed mature gastric teratoma. The formation of a gastroduodenal bulb fistula with the tumour as a bridge is a rare phenomenon. A notable finding of the present case study was that the final diagnosis of gastric teratoma mainly depended on pathological examination.